Le sanctuaire de la Fermerie à Juvigné (Mayenne), de l’âge du Fer à l’époque romaine - Stanislas Bossard; Gérard Aubin; Jacques Meissonnier (Gallia)
Investigations as well as pedestrian survey were carried out in the late 1980s at the site of la Fermerie at Juvigné (Mayenne). It has recently been subject of a new document review. Hardly recognized, the structures recall a Roman sanctuary and the finds characterize cult activities. A large series of Roman and Celtic coins – some of which are mutilated – and also model items, figurines and brooches, as well as weapons and Celtic ornaments constitute offerings deposited during the early Roman period and even from the Late Iron Age. This case is not isolated at the scale of western France; it fits in a corpus of cult sites where religious practices seem to take roots in the Celtic period.